Gestalt Counseling for Bullying Cases in Indonesia: A Literature Review - Haryadi, Rudi; Abidarda, Yulizar (Universitas Negeri Medan, 2024)
This research aims to confirm the usefulness of Gestalt Counseling empirically through a literature review of a number of relevant scientific literature. This research uses a literature review method. In this case, the researcher collected a number of literatures in the form of scientific articles related to Gestalt Counseling for bullying cases in Indonesia during the last 5 years, namely in the period 2018 to 2023. The researcher conducted a search for scientific literature using the Google Scholar, Publish or Perish, and databases. Lens.Org. Of the 23,181 titles, 8 scientific articles were found that best suited the research criteria. The research results show that Gestalt Counseling can be carried out in individual or group formats to increase self-esteem and self-control, as well as reduce levels of depression for victims of bullying. Apart from that, Gestalt counseling can also be applied to reduce aggression, violence and bullying behavior in bullies. It is recommended that further research examine issues related to multicultural factors in Gestalt counseling for this population, the effects of other Gestalt techniques in interventions for victims and perpetrators of bullying, as well as the phenomenological experiences of victims and perpetrators of bullying in receiving Gestalt Counseling.